A Case of Classic Raymond Syndrome. (6th August 2012) - Zaorsky, Nicholas George; Luo, Jin Jun
Abstract : Classic Raymond syndrome consists of ipsilateral abducens impairment, contralateral central facial paresis, and contralateral hemiparesis. However, subsequent clinical observations argued on the presentation of facial involvement. To validate this entity, we present a case of classic Raymond syndrome with contralateral facial paresis. A 50 year-old man experienced acute onset of horizontal diplopia, left mouth drooling and left-sided weakness. Neurological examination showed he had right abducens nerve palsy, left-sided paresis of the lower part of the face and limbs, and left hyperreflexia. A brain MRI showed a subacute infarct in the right mid-pons. The findings were consistent with those of classic Raymond syndrome. To date, only a few cases of Raymond syndrome, commonly without facial involvement, have been reported. Our case is a validation of classic Raymond syndrome with contralateral facial paresis. We propose the concept of two types of Raymond syndrome: (1) the classic type, which may be produced by a lesion in the mid-pons involving the ipsilateral abducens fascicle and undecussated corticofacial and corticospinal fibers; and (2) the common type, which may be produced by a lesion involving the ipsilateral abducens fascicle and undecussated corticospinal fibers but sparing the corticofacial fibers.